Bimtek Pengawasan Pengelolaan Keuangan di Nagari Salimpek Kabupaten Solok Provinsi Sumatera Barat: The Technical Guidance on Financial Management Oversight in Nagari Salimpek, Solok Regency, West Sumatra Province - Sari, Vita Fitria; Fitra, Halkadri; Sebrina, Nurzi; Taqwa, Salma; Cheisviyanny, Charoline; Helmy, Herlina; Syofyan, Efrizal (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The Technical Guidance (Bimtek) on Financial Management Oversight, held in Nagari Salimpek, Solok Regency, West Sumatra Province, aimed to strengthen the capacity of nagari officials in establishing transparent, accountable, and legally compliant financial governance. The activity involved the Nagari apparatus, the Nagari Consultative Body (BPN), and community representatives, with a focus on enhancing knowledge and skills in monitoring, reporting, and controlling the use of Nagari funds. The implementation of Bimtek employed methods such as material delivery, interactive discussions, case studies, and simulations to prepare oversight documents using digital applications. The results indicated an improvement in participants' understanding of village financial management procedures in accordance with Minister of Home Affairs Regulation (Permendagri) No. 20 of 2018, as well as the applicable regulations in Solok Regency and the principles of public accountability. Participants were also able to identify potential risks of fund misuse and develop preventive strategies and effective monitoring mechanisms. Based on the post-activity evaluation, the achievement rates were 87% for knowledge, 85% for skills, and 95% for commitment awareness. This program is expected to serve as a model for continuous capacity-building in other nagaris in Solok Regency, enabling them to achieve professional and integrity-based village financial governance.